AES development in FPGA - Villagarcía Wanza, Horacio A. (2006)
The National Institute of Standards and Technology (NIST) created a new standard known as Advanced Encryption Standard (AES), with the objective of developing the Federal Information Processing Standard (FIPS) which specifies an encryption algorithm capable of protecting sensitive information to be used by the government of the United States. In October 2000, the NIST selected Rijndael as the algorithm proposed for the AES. The algorithm has a round shape made up by three uniform and non-reversible transformations which assures broadcast over the total set of fixed rounds and optimal non-linearity properties. This thesis presents an 8-bit FPGA implementation of the 128-bit block and 128 bit-key AES cipher.